Income Tax Evasion in Uganda - Lakuma, Corti Paul (Economic Policy Research Centre (EPRC), 2019)
Uganda, just as many developing countries, collects less than potential tax. The country compares poorly to other low- income countries with regard to income tax revenue mobilization. This paper estimate the baseline amount of tax owed by comparing income amounts reported on the 2015/16 Uganda Revenue Authority (URA) income tax returns with similar income amounts households reported on the 2015/16 Uganda National Panel Survey (UNPS). The paper also combine the UNPS data and the URA income tax data to estimate potential income tax revenue and the scale of tax evasion in Uganda in 2015/16 by income bracket. The gross tax gap was therefore estimated at Ug.Shs 1, 783.31 billion, or 52.73 percent of the baseline tax. The manufacturing, wholesale and retail, information and communication, financial and insurance, real estate, public administration and human health sectors explain Ug.Shs. 1,512.39 of the tax gap, which is 44.72 percent of the baseline tax. The income bracket above Ug.Shs 410,000 explain more than 80 percent of the sectoral default. Approximately 755,217 persons did not file for income tax in 2015/16, which is 39 percent rate of default. Audit and compliance activities managed to recover Ug.Shs 130.37 billion of Ug. Shs. 1,783.31 billion gross tax gap. We recommend for capacity building in data management and in audit and compliance functions.